Encouraging Landscape Water-Conservation Behaviors #6: Information Seeking Preferences of Florida Residents Who Use Irrigation in the Home Landscape - Courtney Owens; Laura A. Warner; Joy Rumble; Alexa Lamm; Emmett Martin; Randall Cantrell (EDIS, 2015)
How can we encourage Florida residents who irrigate their home landscapes to adopt environmentally responsible irrigation practices? Provide them information they are interested in and deliver it through their preferred information channels. This 5-page fact sheet discusses the topics of interest to this audience and how they prefer to receive information about water-conservation practices related to their home landscaping, and makes recommendations for reaching this audience. Written by Courtney Owens, Laura Warner, Joy Rumble, Alexa Lamm, Emmett Martin, Randall Cantrell, and published by the UF Department of Agricultural Education and Communication, April 2015. (UF/IFAS Photo by Thomas Wright)